The new Koreans the story of a nation - Breen, Michael 1952- (New York Thomas Dunne Books/St. Martin's Press, 2017)
"Just a few decades ago, the Koreans were an impoverished, agricultural people. In one generation they moved from the fields to Silicon Valley. The nature and values of the Korean people provide the background for a more detailed examination of the complex history of the country, in particular its division and its emergence as an economic superpower. Who are these people? And where does their future lie? In this absorbing and enlightening account, Michael Breen provides compelling insight into the history and character of this fascinating nation "--
Map -- Timeline -- A Note About English Spelling of Korean Words -- [I] Portraits -- The Broken Ship -- Out of Gangnam -- The Defiant Land -- The Case for Hanguk -- The Group as Refuge -- Jesus and Local Messiahs -- Suffering in the Republic of Others -- Nationalism and Other Things -- Love and Learning When Your DNA Isn't Yours -- [II] Roots -- Beginnings -- The Quest for Purity -- Being Second Class -- Brothers No More -- [III] Wealth -- Desperation -- Economic Warriors -- The Smell of Money -- The Chaebol Problem -- Work, Work, Work -- [IV] Power -- At Least Pro the Right Kind of Democracy -- Power Shift -- The First Democratic Presidents -- Dissidents in Charge -- Two Steps Back -- [V] Next -- The Miracle of Affirmation -- For Wider Acceptance -- A Wealthier Future -- The Future of Democracy -- Time to Unify?
Includes bibliographical references and index.
Donated by Korean Foundation
Keywords: National characteristics, Korean -- History; Economic development -- Korea -- History; Social change -- Korea -- History; HISTORY / Asia / Korea; Korea -- Biography; Korea -- Politics and government; Korea (North) -- History; Korea (South) -- History; Korea -- Economic conditions -- 1945-.; Korea -- History -- 1945-.